2017
DOI: 10.1111/nmo.13067
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory reflux monitoring for diagnosis of gastro‐esophageal reflux disease: Update of the Porto consensus and recommendations from an international consensus group

Abstract: The consensus group determined that grade C or D esophagitis, peptic stricture, histology proven Barrett's mucosa >1 cm, and esophageal acid exposure greater >6% are sufficient to define pathological GERD. Further testing should be considered when none of these criteria are fulfilled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
336
0
57

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(397 citation statements)
references
References 143 publications
(289 reference statements)
4
336
0
57
Order By: Relevance
“…1 An increase in frequency, duration and amount of reflux, and/or an inability to clear refluxed content can lead to gastroesophageal reflux disease (GERD). 1 An increase in frequency, duration and amount of reflux, and/or an inability to clear refluxed content can lead to gastroesophageal reflux disease (GERD).…”
Section: Introductionmentioning
confidence: 99%
“…1 An increase in frequency, duration and amount of reflux, and/or an inability to clear refluxed content can lead to gastroesophageal reflux disease (GERD). 1 An increase in frequency, duration and amount of reflux, and/or an inability to clear refluxed content can lead to gastroesophageal reflux disease (GERD).…”
Section: Introductionmentioning
confidence: 99%
“…The question to be answered by the clinician is when and how to perform reflux monitoring (on or off PPI; pH-metry or pH-impedance), and finally led to the concept of unproven and proven GERD in the consensus statement [16].…”
Section: Definition Of Distinct Clinical Settings Of Unproven and Promentioning
confidence: 99%
“…Kandulski/Moleda/Müller-Schilling Visc Med 2018;34:97-100 98 in the field updated the recommendations regarding indications, interpretation, diagnosis, and classification of GERD subtypes [16,17]. One of the most important advances in clinical decision making and management is the differentiation of patients with unproven GERD and proven GERD in patients with endoscopic or physiological evidence of GERD, which directs esophageal reflux monitoring on or off PPI therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified that one of the common clinical manifestations of atypical GERD is chronic cough [5]. There are reports of refractoriness when, in the treatment of GERD, the patient remains symptomatic even when using medication and this is very common in atypical GERD [4]. In some cases the treatment of this disease has a high cost and the patient may present side effects due to the treatment [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptom of GERD is heartburn, which, while rarely life-threatening, can greatly reduce a patient's quality of life by affecting daily activities, sleep and what they can eat [1,2]. A systematic review found the prevalence of GERD to be 10-20% of the Western world with a lower prevalence in Asia [3,4]. Typically, the diagnosis of GERD is based on heartburn and acid regurgitation; however, research findings suggest that extraesophageal signs and symptoms are frequent in clinical practice.…”
Section: Introductionmentioning
confidence: 99%